Cultivating better learning attitudes: a preliminary longitudinal study. (4th May 2018) - Hui, Yan Keung; Mai, Bo; Qian, Sheng; Kwok, Lam For
Abstract: The use of flipped classrooms, blended learning environments and the application of technology has been extensively studied and reported in the literature, but the impact of learning activity design on cultivating better learning attitudes has rarely been explored. A rapid adoption of 'e-schoolbag' in basic education in China has been observed in recent years. Its impact on academic performance varies from different ways of e-schoolbag adoption. We conducted a two-year longitudinal study to review the relationship between learning behaviours and academic performance in a primary school with a blended learning environment, and investigated how interventions through learning activity redesign could improve the academic performance by cultivating better learning attitudes. The results show that learning attitudes are positively related to academic performance with proper learning activity design. It is therefore suggested that teachers' interventions through learning activity redesign can cultivate better learning attitudes and thus improve academic performance for learners.